Os conhecimentos tradicionais dos(as) erveiros(as) da Feira do Ver-o-Peso (Belém, Pará, Brasil): um olhar sob a ótica da Ciência da Informação - DANTAS, Cleide Furtado Nascimento (2014)
Study about the traditional knowledge gotten by the herb sellers of the Ver-o-Peso free market, in Belém, Pará, Brazil. On the whole, it aims to contribute with the theme in the perspective of the Information Science. From the point of view of the investigation, it uses the bibliographic and ethnographic research towards the comprehension of the process of acquisition, warehousing and transference of the information about plants, peels and medicinal roots traded by the authors in focus. It verifies that the acquisition and the transmission of this knowledge occurs by the observation and by the orality in the day-to-day contact of the work with those products, kept only in the memory of the owners. Finally, this study shows the risks that permeate the traditional knowledge of the herb sellers of the Ver-o-Peso free market and the possibilities that the theme offers to the Information Science.